2022
DOI: 10.3390/cancers14153839
|View full text |Cite
|
Sign up to set email alerts
|

CAR-NK Cells: A Chimeric Hope or a Promising Therapy?

Abstract: Immunotherapy with chimeric antigen receptor-engineered T cells (CAR-T) has revolutionized the treatment landscape of relapsed/refractory B-cell malignancies. Nonetheless, the use of autologous T cells has certain limitations, including the variable quality and quantity of collected effector T cells, extended time of cell processing, limited number of available CAR cells, toxicities, and a high cost. Thanks to their powerful cytotoxic capabilities, with proven antitumor effects in both haploidentical hematopoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 59 publications
(61 reference statements)
0
12
0
Order By: Relevance
“…Other studies worth mentioning include the successful use of autologous iPSC-derived platelets for the treatment of aplastic anemia [149] and the derivation of an off-the-shelf allogeneic chimeric antigen receptor (CAR) T-cell therapy targeting B-cell malignancies developed by Fate Therapeutics (NCT04629729). An iPSC-derived, off-the-shelf, CAR natural killer (NK) cell therapy is currently being tested in a Phase I clinic trial for refractory B-cell lymphoma (NCT 04245722) and is showing promising therapeutic efficacy [150]. Other studies have been reviewed by Kim et al [99].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies worth mentioning include the successful use of autologous iPSC-derived platelets for the treatment of aplastic anemia [149] and the derivation of an off-the-shelf allogeneic chimeric antigen receptor (CAR) T-cell therapy targeting B-cell malignancies developed by Fate Therapeutics (NCT04629729). An iPSC-derived, off-the-shelf, CAR natural killer (NK) cell therapy is currently being tested in a Phase I clinic trial for refractory B-cell lymphoma (NCT 04245722) and is showing promising therapeutic efficacy [150]. Other studies have been reviewed by Kim et al [99].…”
Section: Discussionmentioning
confidence: 99%
“…While CAR-T treatments have shown significant promise as a novel therapy in relapsed and refractory hematological malignancies, treatment can be limited by the logistical issues of autologous CAR-T production and the inherent risk of GVHD with alloCAR-T. Consequently, natural killer CARs (CAR NK) offer a potential alternative therapeutic strategy [ 100 , 101 ].…”
Section: Emerging Strategies To Improve Car-t Efficacymentioning
confidence: 99%
“…NK cells are part of innate immunity, with the ability to kill tumor cells without any prior activation or expression of MHC molecules, through cytotoxic secretion of perforin/granzyme granules that induce apoptosis [ 101 ]. In ALL, the presence of NK cells in the bone marrow was associated with better prognosis and response to chemotherapeutic agents [ 102 ].…”
Section: Emerging Strategies To Improve Car-t Efficacymentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, keeping in mind all these considerations, the NK-92 cell line is an attractive platform for off-the-shelf CAR therapy since it also avoids the graft/host reaction. In fact, several clinical studies have shown the effectiveness of engineered NK-92 cells against a variety of cancers, including blood malignancies and solid tumors [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%